2023
DOI: 10.2147/jaa.s378505
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Claims Database Study to Clarify Disease Burden of Severe Asthma Patients with Type 2 High or Low Inflammation

Abstract: Purpose The disease burden of severe asthma patients stratified by type 2 (T2) biomarkers is not well studied in large patient samples, especially for T2-low severe asthma patients. Using a Japanese medical record database, we investigated disease and economic burdens in T2-high and T2-low severe asthma patients. Patients and Methods Data of severe asthma patients (receiving high-dose inhaled corticosteroids and additional asthma-related controller medications or oral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
0
1
Order By: Relevance
“…The prevalence of severe asthma patients with low type 2 asthma usually ranges from 15% to 30%. [20][21][22] In our study, this prevalence was much lower (i.e. 5.1%) because the criteria for low type 2 asthma were more restrictive.…”
Section: Discussioncontrasting
confidence: 59%
“…The prevalence of severe asthma patients with low type 2 asthma usually ranges from 15% to 30%. [20][21][22] In our study, this prevalence was much lower (i.e. 5.1%) because the criteria for low type 2 asthma were more restrictive.…”
Section: Discussioncontrasting
confidence: 59%
“…A Finnish study from 2020, 15 also analysed severe asthmatic patients with high b-eos (≥300 cells/μL) and showed that these patients had a 1.4 to 1.7-fold increase in all-cause and asthma-related outpatient visits and inpatient days. A study from Japan from 2023, 16 analysing severe asthma patients stratified by the T2 biomarkers b-eos and total IgE, showed no statistical difference in asthma-related exacerbations or medicine costs.…”
Section: Introductionmentioning
confidence: 99%